Some Polemical Emphases in the "Sefer Miṣwot Gadol" of Rabbi Moses of Coucy - Woolf, Jeffrey R. (The Jewish quarterly review, 1998)
The "Sefer Miṣwot Gadol" of R. Moses b. Jacob of Coucy has long been recognized as a distinctive product of the period of the Tosafot. This study examines the work in the context of reactions to the church's onslaught against the Talmud. It is argued that the Introduction to "Sefer Miṣwot Gadol" constitutes a response to, and refutation of, the articles of indictment against the Talmud presented at the Paris disputation of 1240. In addition, certain emphases within the work itself may similarly be understood within the context of the ecclesiastical campaign against the oral law.